THE EVOLVING KNOWLEDGE BASE ON PRINCIPAL LEADERSHIP RESEARCH: A BIBLIOMETRIC ANALYSIS OF THE LITERATURE 2013-2022 - Suhaibah Mukhtar; Ahmad Zabidi Abdul Razak (Journal of Islamic, Social, Economics and Development, 2023)
This paper provides a thorough examination of contemporary research on principal leadership within the realm of education, employing a bibliometric analysis. Principals wield a crucial influence on shaping school culture, climate, and overall effectiveness. The review consolidates findings from diverse studies investigating various facets of principal leadership, exploring the influence of leadership styles on teacher morale, student achievement, and overall school enhancement. Additionally, the paper delves into the role of principals in fostering positive school climates, managing change, and cultivating collaborative relationships within the school community. A comprehensive review of articles on principal leadership available in the Scopus database between 2013 and 2022 was undertaken. Utilizing the keyword "Teacher Professional Learning," 661 articles were gathered for further scrutiny. Various tools, including Microsoft Excel for frequency analysis, for data visualization, and Harzing's Publish or Perish for citation metrics and analysis, were employed throughout the analytical process. By dissecting the existing body of literature, this paper aims to deepen our understanding of the multifaceted nature of principal leadership, providing insights for both researchers and practitioners. The study analysed bibliometric indicators such as language, subject area, research trends by publication year, top countries, the most influential institution, active source title, citation analysis, authorship analysis, and keyword analysis. The findings indicate a significant growth rate in literature on principal leadership from 2013 to 2022, with the United States emerging as the largest contributor to research on educational leadership, closely followed by the United Kingdom. In conclusion, the synthesis of current research on principal leadership offers valuable implications for the ongoing professional development of school leaders and the formulation of policies that support effective leadership practices. As education systems strive for continuous improvement, a robust understanding of principal leadership is essential for creating learning environments that foster student success and holistic school development.